Про датування пожежі на укріпленнях фортеці XVII— XVIII ст. у с. Білики - Калашник, Є.С. (Археологія, 2009)
У статті подано аналіз шару, який утворився внаслідок пожежі на укріпленнях пізньосередньовічної фортеці сотенного містечка Білики Полтавського полку (тепер смт Білики Кобеляцького р-ну Полтавської обл.), і запропоновано кілька вірогідних дат руйнації укріплень. Освещены материалы разведок 2008 г. на укреплениях позднесредневекового сотенного местечка Белики (теперь пгт Белики Кобелякского р-на Полтавской обл.). Объектом исследования стал слой обожженного грунта, зафиксированный в стратиграфической колонке зачистки вала и интерпретированный как следы набега. Выяснен ряд соответствий этому факту среди исторических событий второй половины XVII — первой половины XVIII вв. На основе изучения военных походов и кампаний на территории края в обозначенный период предполагается, что нападение на казацкий форт, зафиксированное археологически, произошло в одну из следующих дат: 15 (25) мая 1658 г., в начале февраля 1675 г., в конце января 1693 г., в январе же 1696 г., в рамках апрель—июль 1709 г. или же в начале февраля 1737 г. Набег мог быть совершен как татарскими ордами, так и частями русской армии. Говорить об этом, как и о более конкретной интерпретации факта вооруженного погрома крепости, пока преждевременно. Materials of 2008 archaeological prospecting at the fortifications of the Late Mediaeval company town Bilyky (Bilyky Village of Kobelyaky Region in Poltava Oblast now) are described here. The matter of a study was a layer of a burnt soil set in the stratigraphic column of the rampart clearing and interpreted as traces of the incursion. Several correspondences to this fact were identified among the historic events of the second half of the 17 th through the first half of the 18 th centuries. Basing on the study of campaigns on the territory of a region during the earmarked period it is resumed that the attack on the Cossacks’ fort which was evidenced archaeologically took place at one of the following dates: May, 15 (25) of 1658, in the beginning of February of 1675, at the end of January of 1693, January of 1696, from April to July of 1709 or at the beginning of February of 1737. The assault might have been made by Tatar hordes or by Russian army units. It is too early yet to talk about more precise interpretation of the fact of armed defeat of the fortress.